The practice of conservation from owners perspective / Nor Amalin Keling - Keling, Nor Amalin (Faculty of Architecture, Planning and Surveying, 2013)
Nowadays, conservation remains at the moderate level of knowledge among Malaysian. The issue is they do not care in any conservation works and stated that they do not know about the guidelines in the conservation works of historical buildings. Most of them demolish the old building and replace with a new building. They refuse to restore the old building. This study or research is about the conservation on the old shop houses which is located in most of the old town in every state in Malaysia. Furthermore, the objectives of this study are to identify the conservation guidelines for shop houses in every case study, to examine old shop house owners' conservation practised and also to analyse the problems in conserving old shop houses faced by building owner. A few method were taken to collect the data for this study such as un-structured interview also distribution of the questionnaire. Other than that, site investigation was done in the case studies, data analysis, and recommendation. The main finding o f this study is high cost of conservation works and building owner do not able to cater the cost of any conservation works made to their building. While the main recommendations for this research are financial assistant from NGO and local authority to owners, standardized of conservation guidelines, the awareness and perception of public towards conservation, expertise in conservation, expand the NGOs association, minimum usage of buildings and last but not least is specific maintenance works. In conclusion, the problems and issues of the old shop house with scope of conservation should be well identified and analysed, so that, the recommendation for the better approach towards conservation would be taken.